OCA2 splice site variant in German Spitz dogs with oculocutaneous albinism. - Madleina Caduff (PLoS ONE, 2017)
We investigated a German Spitz family where the mating of a black male to a white female had yielded three puppies with an unexpected light brown coat color, lightly pigmented lips and noses, and blue eyes. Combined linkage and homozygosity analysis based on a fully penetrant monogenic autosomal recessive mode of inheritance identified a critical interval of 15 Mb on chromosome 3. We obtained whole genome sequence data from one affected dog, three wolves, and 188 control dogs. Filtering for private variants revealed a single variant with predicted high impact in the critical interval in LOC100855460 (XM_005618224.1:c.377+2T>G LT844587.1:c.-45+2T>G). The variant perfectly co-segregated with the phenotype in the family. We genotyped 181 control dogs with normal pigmentation from diverse breeds including 22 unrelated German Spitz dogs, which were all homozygous wildtype. Comparative sequence analyses revealed that LOC100855460 actually represents the 5'-end of the canine OCA2 gene. The CanFam 3.1 reference genome assembly is incorrect and separates the first two exons from the remaining exons of the OCA2 gene. We amplified a canine OCA2 cDNA fragment by RT-PCR and determined the correct full-length mRNA sequence (LT844587.1). Variants in the OCA2 gene cause oculocutaneous albinism type 2 (OCA2) in humans, pink-eyed dilution in mice, and similar phenotypes in corn snakes, medaka and Mexican cave tetra fish. We therefore conclude that the observed oculocutaneous albinism in German Spitz is most likely caused by the identified variant in the 5'-splice site of the first intron of the canine OCA2 gene.